Folkmarketing itineraries:: memories, stories and experiences (Revista Internacional de Folkcomunicação, 2022)
This essay intends to bring a memorialistic journey and the evolutions that the Folkmarketing theory has gone through during its 24 (twenty-four) years of existence. Based on a bibliographic review, we seek to understand how the theory construction process took place and the studies on its applicability in public and private organizations. We also postulate, briefly build the bibliometry of the theory and its genealogy. The present essay seeks, at the end of this journey, to open up new possibilities and instigate studies on the current applicability of the theory.